Training of self-confidence and control of anxiety in athletes of the u-16 category of Bogotá D.C. (Impetus, 2022)
Introduction: There are various psychological skills that are considered essential to predict performance in sport, such as self-confidence, motivational levels, emotional control or coping strategies (Berenguiet, et al., 2012). Course objective: Identify and develop a psychological training plan that facilitates the improvement of self-confidence and anxiety control through adequate emotional regulation before competition. Methodology: The approach is quantitative, because the magnitude and quantity of objects of study investigated is explicit in a numerical way (Hernández, 2008). Design: It is experimental, cross-sectional, with the management of independent and dependent variables (Hernández, et al., 2013). Scope of the research: Exploratory, because little information was identified, it is taken as a new study topic (Hernández, et al., 2013, p.72). Databases: The databases used were 4; SportDiscus, Google Scholar, ScienceDirect and ProQuest, a total of 81 articles were found, of which 14 were considered functional. Results: They were positive, it was possible to show that the athletes who were evaluated have high anxiety levels, moments before the competition and that their level of self-confidence is low with respect to the capacities they have according to the training carried out during those weeks. Conclusions: with the psychological training carried out during these weeks, the PAR-P1 test was carried out again, obtaining influential results, thus improving their anxiety levels and their self-confidence when competing.
Keywords: Anxiety; self-confidence; sports psychology; mental training